(untitled) (LEARNing Landscapes, 2012)
In this paper, I have made a case for using creative approaches to facilitate educational transitions. I have presented examples from research and practice which suggest that creative activities can be used in multiple ways to portray children and young people’s voices. I argue that these voices, as well as the process of being heard, can help modify existing transition practices, identify new transition practices, and enhance children and young people’s ability to manage change. Theories of self-esteem, resilience, and emotional intelligence have been used to explain the psycho-social processes that a child, or young person, goes through during transitions, as well as how creative approaches can be used to support these processes.